The potential role of BCL2A1⁺ tissue-resident macrophages in the prognosis of Wilms tumor - Wei Wang; Xianwu Yang; Zhihui Zhu; Zhishen Tang; Yingquan Zhuo; Jun Du; Yuxian Zhu; Xi Luo; Jingjing Xiao; Huajian Gu (European Journal of Medical Research)
Abstract Tumor-associated macrophages (TAMs) have a significant impact on the prognosis and treatment outcomes of Wilms tumor (WT) patients. To explore the key mechanisms underlying WT progression and immune therapy, this study used CIBERSORT to analyze the immune cell infiltration of 120 WT patients. Combined with single-cell RNA sequencing (scRNA-seq) data, the heterogeneity of macrophages in WT and adjacent tissues was revealed, identifying a subpopulation of tissue-resident macrophages with specific expression of BCL2A1. Further validation through immunohistochemistry (IHC) and immunofluorescence (IF) experiments confirmed the presence of BCL2A1⁺tissue-resident macrophages and elevated BCL2A1 expression is associated with advanced tumors and poor prognosis. Functional enrichment analysis suggests that BCL2A1⁺tissue-resident macrophages may promote WT progression through immune regulation and apoptosis pathways. This study is the first to identify the presence of a BCL2A1⁺tissue-resident macrophage subset in WT and reveal its critical role in tumor progression, potentially providing a novel target for personalized immunotherapy.